Rhetorical and Content Devices for Inviting Collective Applause in Benjamin Netanyahu’s Congress Speeches - Gharabeh, Thaher (International Journal of Language and Literary Studies, 2024)
This study focuses on the rhetorical and content devices used to elicit collective applause in political discourse of conflict, specifically in two speeches delivered by Israeli Prime Minister Benjamin Netanyahu to the Congress in 2015 and 2024. The study aims to recognise the employed devices, the aims of the speaker for employing the devices, and to find the difference in applause durations among the used devices. 114 instances of collective applause were collected from authorised resources to be investigated. The study finds the content device ’advocacy for certain policy in the future’ to be the most frequent in the 2015 speech, while the rhetorical device ’headline-punchline’ is the most frequent in the 2024 speech. Moreover, the speaker uses each device to assert certain ideas and to attain a different main aim later, which can be located in advocating a certain policy in the future. The policies that the speaker advocated are mainly related to the sustainability of American support for Israel and to conflict resolution from Netanyahu’s perspective. Further, in the 2015 speech, the highest instances had the greatest total applause; however, in the 2024 speech, the devices with the highest instances do not have the greatest total of applause duration, which signifies the impact of the device content and context in eliciting collective applause.